Leer para escribir la historia natural americana : los jesuitas Clavijero, Molina y Velasco - Kenya Bello (Nuevo mundo - Mundos Nuevos, 2017)
The written character of history is one of the aspects that defines it as a field of knowledge. This is precisely the reason that historiography reflects on History’s writerly dimension. However, it is important to consider that the historian has also been, for several centuries, a reader. This research assumes that in the case of the Spanish-American Jesuits, authors of natural histories in the eighteenth century, writing is also a form of reading. Therefore, it explores the natural histories of Clavijero, Molina and Velasco in search of what they read, the way they read it and the places where they read it. These insights will allow us better to understand how they developed their historiographical practice. The pages that follow thus intend to bring closer together the study of historical writing and the cultural history of reading.